Some New Iterated Hardy-Type Inequalities - A. Gogatishvili; R. CH. Mustafayev; L.-E. Persson (Journal of Function Spaces and Applications)
We characterize the validity of the Hardy-type inequality ∥∥∫s∞h(z)dz   ∥p,u,(0,t)   ∥q,w,(0,  ∞)≤c  ∥h∥θ,v(0,∞), where 0<p<∞, 0<q≤∞, 1<θ≤∞, u, w, and v are weight functions on (0,∞). Some fairly new discretizing and antidiscretizing techniques of independent interest are used.